Influence of different types of light curing units and photoinitiators in microhardness and color of composite resins after immersion in wine - Souza, Morganna Borges de Almeida [UNESP]; Briso, André Luiz Fraga [UNESP]; Ramos, Fernanda de Souza Silva [UNESP]; Reis, Bruna de Oliveira [UNESP]; dos Santos, Paulo Henrique [UNESP]; Fagundes, Ticiane Cestari [UNESP] (Editora Cubo, 2019)
Objective: the aim of this study is to evaluate the microhardness and color change (δE) of composite resins, that were light-cured with different LEDs, after being immersed in a staining drink. Material and Methods: Two composite resins with Lucerin-TPO (Tetric N-Ceram/Vit-l-escence) and camphorquinone (Filtek Z350) were selected. The specimens (n=120) were prepared and lightcured with LED of monowave or polywave lightemitting diode (LED) devices. Microhardness and color evaluations were measured before and after immersion in staining drink. Microhardness data were evaluated by Kruskal-Wallis test, Mann- Whitney and Wilcoxon tests. Color changes were evaluated by two-way analysis of variance (ANOVA) and Tukey test (p ≤ 0.05). Results: No statistically significant difference between the two generations of LEDs was found for microhardness data. Regarding the δE, a statistical difference between the two LEDs was observed for Tetric NCeram and Filtek Z350. Conclusion: The compostion of composites appears to have more influence on analyses than the type of LEDs used. A decreased microhardness occurred to Vit-lescence for monowave and to Filtek Z350 for both LED devices. A clinically perceptible color change was observed for Tetric-N Ceram and Filtek Z350 when polywave LED were used.
Influencia dos diferentes tipos de unidade fotoativadoras e fotoiniciadores na microdureza e cor de resinas compostas após imersão em vinho
Keywords: Composite resins; Curing lights; Dental resin; Photoinitiators; Resin photoinitiators